DINAMIKA IJTIHAD ULAMA INDONESIA DALAM FORMALISASI HUKUM ISLAM - Putra, Muh Yunan (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
Indonesia is the one of democracy country and has principle of believe in the One Supreme God. Refer to it, there are some roles or the bills created based on Islamic Law, such as Marriage Law, Heritage Law, Waqf Law and Criminal Law. In apply, Islamic Low usually face the normative situation and the increasing of human need and thinking. So, it is required to be able to adjust or create new form to fulfill both of interest. In this case, it can be seen at product law or fatwa created by Indonesian Council Of Ulama (MUI) which integrated based on community’s need. However, disconnected between structure and function of law caused by political performance. Historically, Islamic Law in Indonesia was influenced by social-culture aspect, it marge with Islamic thinking and characteristic such as Fiqh Book, Islamic roles in Muslim’s country, judgment or verdict, or the roles (fatwa) which is created by Ulama. So, namely Islamic Law is the pure of Islamic thinking which produced by Ulama integrated with the social environment. Although, al-Quran dan al-hadits have the roles also to be law, but there are many problems that need to solve using the law’s guide. To solve that problems, Ulama do ijtihad and think hard to get out problem solving. Finally, Ulama use their mind to fulfill the emptiness law, so the result is the product of thinking law as now as.